2010
DOI: 10.1053/j.gastro.2009.11.053
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin and Related Compounds Are Direct Inhibitors of Hepatitis C Virus RNA-Dependent RNA Polymerase

Abstract: Silibinin A and silibinin B, as well as Legalon SIL, inhibit HCV replicon and JFH1 replication in cell culture. This effect is at least partly explained by the ability of these compounds to inhibit HCV RNA-dependent RNA polymerase activity. Our results provide a basis for the optimization and subsequent development of members of the Flavonoid family as specific HCV antivirals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
2
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(113 citation statements)
references
References 31 publications
3
104
2
2
Order By: Relevance
“…Recently, attention has focused on silybin's effects on HCV replication [43][44][45][46]. In this study we found no notable changes in HCV RNA in patients treated with the stated dose of silybin (data not shown).…”
Section: Discussionmentioning
confidence: 37%
“…Recently, attention has focused on silybin's effects on HCV replication [43][44][45][46]. In this study we found no notable changes in HCV RNA in patients treated with the stated dose of silybin (data not shown).…”
Section: Discussionmentioning
confidence: 37%
“…In addition, Silibinin A and silibinin B also decreased HCV genotype 1b replication and HCV genotype 2a strain JFH1 replication in cell culture. Interestingly, none of these agents affected the HCV protease function [59] . The antioxidant effects of silibinin have been showed in several cell studies.…”
Section: Silymarin Complexmentioning
confidence: 99%
“…There have been many species of milk thistle reported, and these plants contain secondary metabolites such as glycosides, bioactive azo compounds, flavonoids, flavanolignins (silymarin) and rosmarinic acid. These metabolites are important pharmaceutical agents for the treatment of lung and colon cancers, such hepatitis (Eşiyok et al, 2004;Liu et al, 2007;Ahmed-Belkacem et al, 2010). Polyphenols are a wide family of natural substances, contains many subunits such as phenolic acids, flavonoids, procyanins, anthocyanins, tannins and lignins.…”
Section: Introductionmentioning
confidence: 99%